Polygraph and Reliability in Psychological Assessment: Myth or Reality? - Kron, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
The purpose of this paper is to enlighten that every statement or conclusion of reliability of a poligraph is a high-risk statement. After introductory historical remarks, this paper discusses and analyses empirical evidence of the validity and reliability of polygraph testing, a silent lie detector, as an alternative procedure. In a respectable academic article, "Charlatanry in forensic speech science" (Eriksson & Lacerda, 2007), the authors reviewed 50 years of lie detector research and came to the conclusion that there is no scientific evidence supporting that lie detectors actually work. According to the American Psychological Association (APA, 2014 and 2013), "most psychologists agree that there is little evidence that polygraph tests can accurately detect lies". As a result of those findings, APA, as an academic publisher, has removed scientific articles which used the results of polygraph research as empirical argumentation from online databases. Ergo, accumulated empirical evidence suggests that instruments like polygraph don't detect lies, in statistical terms, more than random guessing.